2004
DOI: 10.1158/1078-0432.ccr-0930-03
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Expression of Neuropilin-1 and -2 in Human Pancreatic Cancer Cells

Abstract: Purpose: Neuropilin (Np)-1 and -2 are coreceptors for vascular endothelial growth factor (VEGF). This study was designed to assess their role in pancreatic ductal adenocarcinoma (PDAC).Experimental Design: We assessed Np-1 and Np-2 expression by real-time quantitative PCR in relation to the expression of VEGF ligands and receptors in pancreatic cancer cell lines and tissues.Results: ASPC-1, CAPAN-1, and PANC-1 pancreatic cancer cells and tumor-derived, laser-captured pancreatic cancer cells exhibited higher Np… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 43 publications
2
92
0
Order By: Relevance
“…NO synthesis can be induced by interaction of L1CAM and neuropilin-1 on one cell (cis) or by interaction of both molecules on different cells (trans). Moreover, it has been shown that PDAC cells highly express neuropilin-1 (Fukahi et al, 2004) and that overexpression of neuropilin-1 is able to induce chemoresistance in PDAC cells (Wey et al, 2005). As both PT45-P1res and PT45-P1 cells exhibit neuropilin-1 expression (unpublished observation), it seems likely that cis and trans interactions of neuropilin-1 with L1CAM increase iNOS expression and NO synthesis, thereby leading to chemoresistance in PT45-P1res cells.…”
Section: Discussionmentioning
confidence: 91%
“…NO synthesis can be induced by interaction of L1CAM and neuropilin-1 on one cell (cis) or by interaction of both molecules on different cells (trans). Moreover, it has been shown that PDAC cells highly express neuropilin-1 (Fukahi et al, 2004) and that overexpression of neuropilin-1 is able to induce chemoresistance in PDAC cells (Wey et al, 2005). As both PT45-P1res and PT45-P1 cells exhibit neuropilin-1 expression (unpublished observation), it seems likely that cis and trans interactions of neuropilin-1 with L1CAM increase iNOS expression and NO synthesis, thereby leading to chemoresistance in PT45-P1res cells.…”
Section: Discussionmentioning
confidence: 91%
“…Accumulating evidence suggests that neuropilin-1 is overexpressed in several cancers and its high expression is correlated with poor prognosis (Ding et al, 2000;Kawakami et al, 2002;Roche et al, 2002;Vanveldhuizen et al, 2003;Broholm and Laursen, 2004;Fukahi et al, 2004;Li et al, 2004;Osada et al, 2004;Parikh et Figure 8 Semaphorin3A (Sema3A) expression in human glioblastoma multiformes (GBMs). (a) Immunohistochemical analysis of Sema3A in human GBM tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, genetic targeting of VEGF-RII has been shown to inhibit local growth and metastatic spread of pancreatic cancer cells. 69 Other angiogenic proteins that have been identified as negative prognostic factors in PDAC include cyclooxygenase-2, 70 neuropilin-1 (NRP-1), 71 and others. Interestingly, angiogenic receptors may not only be expressed on endothelium but are also present and functional in pancreatic cells.…”
Section: Endothelial Cells and Angiogenesismentioning
confidence: 99%